Nilai Budaya Dan Kearifan Lokal Dalam Membentuk Budaya Hukum Pada Masyarakat Adat Kampung Pulo - Neneng Tripuspita (Lembaga Pengembangan Kinerja Dosen, 2024)
Culture is a product of human knowledge as social beings, that knowledge is not obtained through genetic inheritance in the human body, but is obtained through the position of humans as social beings which is an experience through a learning process.It is in this context that the research was conducted to see how indigenous peoples as a minority group internalize their cultural values ​​into cohesive values ​​and reflect their strong character. The indigenous peoples in Pulo Village, Cangkuang Village, Leles District, Garut Regency, West Java Province, are a group of indigenous people who continue to internalize and preserve traditional values ​​into the character of their community members. This type of research uses a qualitative approach with an ethnographic type, namely research conducted in certain indigenous communities. The objectives to be achieved in this research are to briefly describe the internalization of cultural values ​​of the traditional village communities that can be promoted as the basis for forming the character of the Indonesian nation and internalizing organizational values. Based on the analysis of various facts related to Pulo village, it can be concluded that cultural values ​​can use the values ​​of local wisdom that develop in the community in a comprehensive manner capable of providing data in shaping legal culture and forming strong characters in upholding culture. This helps the community in developing such culture-based laws.